User Acceptance Model for Assessing Trust on Electronic Transaction Succession - Durachman, Yusuf; Nanang, Herlino; Misman, Ahmad F; Zulkifli, Zahidah (International Journal of Integrated Engineering, 2019)
Trust is very important for the sustainability of an online business. Take care of the trust of customers is a must for an online store that is very different from the normal physical store. Due to a number of situations, the seller and the buyer cannot meet in person, the customer cannot see the products we sell directly and the payment process must be through a bank transfer or with an online payment system. This study report and combine technology acceptance model within an information system (IS) success model in the context to assessing trust on electronic transaction succession. The researcher has developed the model base on the input-process-output the IS success models. Study observes how trust and risk affect an Internet consumer’s related with intention to use. Development of theoretical framework de- scribing that trust making process a consumer uses when purchase. Success of an electronic transaction on many factors, one of the important is trust. Acquiring customer trust depends on many things such as web site, quality service, and trust tendency. This paper analyses the role of trust from the transaction perspective to building customer trust.